Rare case of mesocardia with ostium secundum ASD and double IVC. Issue 4 (25th April 2022) - Kumar, Shriram; Nandyal, Shreyas Raghavan; Kaushik, Sharanya; Ibrahim, Sufyan
Abstract : We report an extremely rare case of mesocardia with double inferior vena cava (IVC) in this case report. The patient's associated atrial septal defect (ASD) with left to right shunt leading to pulmonary congestion and recurrent episodes of pneumonia was the leading diagnosis for which care was sought at our hospital. The diagnoses of these rare congenital cardiac anomalies were uncovered only after a thorough workup. Mesocardia is extremely rare and accounts for only 0.2% of congenital anomalies. Its association with other cardiac and vascular anomalies, however, warrants a meticulous workup for the identification of such associated conditions—ASD and double IVC being two such anomalies in our patient. The dictum of working up a case of congenital cardiac anomaly for other congenital cardiaovascular anomalies, therefore, found merit in our case.